1997
DOI: 10.1161/01.atv.17.11.3321
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Factors as Predictors of Ischemic Heart Disease and Stroke in the Edinburgh Artery Study

Abstract: Plasma fibrinogen is a consistent predictor of ischemic heart disease (IHD) in prospective studies, but there are fewer data relating other hemostatic variables to IHD and also to stroke. We therefore studied the relationships of plasma fibrinogen, von Willebrand factor antigen, tissue plasminogen activator (TPA) antigen, factor VII, and fibrin D-dimer to incidence of IHD and stroke and determined whether any associations could be explained by conventional risk factors and baseline heart disease. In the Edinbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
248
6
10

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(280 citation statements)
references
References 30 publications
16
248
6
10
Order By: Relevance
“…24 However, among the studies included in this analysis, the predictive ability of vWF depends strongly on the variables controlled for. [11][12][13][14][15]24 The precise mechanism by which vWF is associated with cardiovascular risk is unclear. vWF, an acute-phase reactant, could be only a marker of the inflammatory process, which is known to play a major role in CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 However, among the studies included in this analysis, the predictive ability of vWF depends strongly on the variables controlled for. [11][12][13][14][15]24 The precise mechanism by which vWF is associated with cardiovascular risk is unclear. vWF, an acute-phase reactant, could be only a marker of the inflammatory process, which is known to play a major role in CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies of vWF conducted in healthy individuals are available but have produced mixed results. [11][12][13][14][15] Only a few data are available for TFPI in humans: f-TFPI levels are elevated in patients with unstable angina and increase the risk of a poor outcome. 16 Very recently, a case-control study indicated that low levels of f-TFPI were a risk factor for deep vein thrombosis.…”
mentioning
confidence: 99%
“…5 Similarly, elevations of Ddimer are associated with increased risk of future myocardial infarction, stroke, and peripheral vascular disease. 6 Several studies have shown that essential hypertension is associated with increased levels of plasma fibrinogen and D-dimer, indicating a decreased fibrinolytic capacity. 4 Hovewer, there has been no study about levels of plasma fibrinogen and D-dimer in subjects with WCHT in the literature.…”
mentioning
confidence: 99%
“…Most of them have demonstrated weak associations of vW levels with the risk of CHD, turning into insignificant after adjustment for conventional risk factors [23,30,135,137,[141][142][143]. A large prospective study yielded encouraging results showing a moderately significant association between vW and CHD even after adjustment for baseline values of classical risk factors (OR in the top vs. the bottom third 1.82, 95% CI 1.37-2.41) [144].…”
Section: Von Willebrand (Vw)mentioning
confidence: 99%